LOGICAL FALLACY ON GOVERNMENT POLICY AND GOOD GOVERNANCE IN INDOPOS.CO.ID MEDIA - Haris Ahmad Rizal; Maulana Rifai; Gun Gun Gumilar (Program Studi Ilmu Pemerintahan Universitas Muhammadiyah Buton, 2021)
The relocation of the capital city to an area is considered to encourage faster and cleaner state governance. The purpose of this research is to find out whether the case is a hoax, gimmick, and victim playing, to find out the government's problems related to the case, and to find out whether the problem is a logical fallacy or not. Informants from the results of this study are articles from Indopost.com that research results can guarantee that for the purpose of moving the capital city, the central government creates services that make it easier for the community to manage and generate logical errors. Inappropriate, D1 Argument From Ignorance. This news results in the conclusion that this news is not included in Hoax, Gimmick, and Playing Victim because the argument is positive. The relocation of the capital city is expected to be able to provide positive results for the progress of the Indonesian state and make DKI Jakarta a business city for economic growth in Indonesia.